POTENSI EKSTRAK Jatropha multifida TERHADAP EKSPRESI VEGF APHTHOUS ULCER Rat norvegicus - Ch. Destri Wiwis Wijayanti; I Ketut Sudiana; Jusak Nugraha (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
Aphthous ulcer is the most common oral mucosal disease occurring in up to 25% of the world's human population. In general, therapy is more directed to pain control and hope of faster healing. Increased use of the drug with the original content on the grounds more free toxic effects, easy to obtain and affordable prices cause the use of plants as ingredients of medicine to be an alternative choice. Jatropha multifida known as betadin plant is a plant with bioactive ingredients flavonoids, diterpenoid, tannins and saponins have been widely used as medicinal plants.Research on aphthous ulcer in mouth mucosal of Rat norvegicus was made by using heated burnisher and using 54 Rat norvegicus rats divided into five groups were normal group, K0 (CMC-Na3%), P1 (2.5% JM); P2 (5% JM) and P3 (JM 10%). Giving a topical extract of J.multifida done 2 times a day then sacrificed on day 3 and day 5. VEGF expression in aphthous ulcer in the mouth tissue by immunohistochemical staining. The result of statistical analysis on VEGF expression showed significant difference (p